No baque do Maracatu Nação: movimentos que ressoam uma análise psicanalítica - Gomes, Lahana Sambaquy (My University, 2026)
This study investigates the movements generated by the popular cultural manifestation Maracatu Nação, from Recife, Pernambuco, Brazil. It´s a cultural manifestation of (r)existence for the members of the Maracatu group. National and international artists and researchers are interested in learning about it, and this boosts tourism in the city. The relevance of this cultural expression reinforces the need for more study in the field of Tourism, since few scientific publications in this area of knowledge were found. The investigation of the topic begins with the question: what movements does Maracatu Nação generate from the tourist-cultural scene of Recife, Pernambuco? This question leads to the general objective: investigating what movements Maracatu Nação generates from the tourist-cultural scene of Recife, Pernambuco; and the specific objectives: identifying the definitions that makes the movement a concept; contextualizing Maracatu Nação within the tourist-cultural scene of Recife, Pernambuco; and analyzing what unconscious psychic and social movements emerge in/from Maracatu Nação. To support the analysis, a literature review of scientific production on cultural manifestation in the field of Tourism was conducted, along with a review of the term "movement," to define the meaning for the term in this research, and of the concept of castration in the field of psychoanalysis. The investigation with the psychoanalytic method takes as analytical material the text of three toadas (songs) from the Nação Estrela Brilhante do Recife. In this method, the researcher is guided by the text to construct connections between the content, the literature used in the research, and their theoretical framework, uncovering meanings through their reading. The analysis of the text, articulated with aspects of history, ethnic-racial topic, Tourism, and Psychoanalysis, guides the construction of a metapsychological essay, which points to various effects of movement: geographical, cultural, political, and psychic. Maracatu Nação, in addition to being an expression of faith, presents itself as a response to the symbolic castration imposed by racism. It is a device of (r)existence, whose aesthetic and creative movement seeks to fill the gaps in history that have been erased by hegemonic narratives in education, media, and entertainment. Maracatu Nação provides its members with a space for identification and belonging, enabling movements of reaffirmation of their culture and of what it means to be/become Black. [resumo fornecido pelo autor]
O presente trabalho investiga que movimentos são gerados pela manifestação de cultura popular Maracatu Nação, originada em Recife-PE. Além de ser uma manifestação cultural de (r)existência para os membros das nações, o Maracatu desperta interesse em artistas e pesquisadores nacionais e estrangeiros, e movimenta o turismo na referida cidade. Tal fato demonstra a relevância dessa expressão cultural, reforçando a necessidade do seu estudo no campo do Turismo. A investigação do tema, parte da pergunta: que movimentos o Maracatu Nação gera a partir da cena turístico-cultural de Recife-PE? Tal questão encaminha como objetivo geral: investigar que movimentos o Maracatu Nação gera a partir da cena turístico-cultural de Recife-PE; e como objetivos específicos: apontar os possíveis destinos que tornam o movimento um conceito; contextualizar o Maracatu Nação na cena turístico-cultural de Recife-PE; analisar que movimentos psíquicos inconscientes, e sociais emergem no/pelo Maracatu Nação. Para fundamentar a análise, foi realizada uma revisão bibliográfica da produção científica sobre a manifestação cultural no campo do Turismo, uma revisão dos usos do termo "movimento" apontando os delineamentos de sentido para o termo nesta pesquisa, e do conceito castração no campo da psicanálise. A investigação parte da pesquisa com o método psicanalítico, e toma como material de análise o texto de três toadas (canções) da Nação Estrela Brilhante do Recife. Neste método o pesquisador é conduzido pelo texto, a construir relações de sentido entre o conteúdo, a literatura trabalhada na pesquisa, e ao seu arsenal teórico, desvelando sentidos a partir da sua leitura. A análise do texto, articulado com aspectos da história, das relações étnico-raciais, do Turismo e da Psicanálise, encaminha a construção do ensaio metapsicológico, o qual aponta para diversos efeitos de movimento: geográficos, culturais, políticos e psíquicos. O Maracatu Nação, além de uma expressão de fé, apresenta-se como uma resposta à castração simbólica imposta pelo racismo. Trata-se de um dispositivo de (r)existência, cujo movimento estético e criativo, busca preencher as lacunas da história que foi apagada pelas narrativas hegemônicas na educação, nas mídias, no entretenimento. O Maracatu Nação propicia a seus integrantes um espaço de identificação e pertencimento, possibilitando movimentos de reafirmação de sua cultura e do que é ser/tornar-se negro. [resumo fornecido pelo autor]
Keywords: Turismo cultural - Recife (PE); Maracatu; Psicanálise; Movimento; Cultura popular; Heritage tourism - Recife (Brazil); Maracatú; Psychoanalysis; Motion; Popular culture